Ethanolic Extract of Cyclea barbata Leaves as a Promising Natural Candidate for Anti Peptic Ulcer: Ekstrak Etanol Daun Cyclea barbata sebagai Kandidat Alami Antitukak Lambung - Puspita Sari, Dyah Ratna Ayu; Ugrasena, Putu Yudha; Mahayani, Ni Putu Rika (Universitas Tadulako, 2025)
Background: Peptic ulcer disease (PUD) was a persistent gastrointestinal disorder characterized by mucosal damage in the stomach or duodenum. Cyclea barbata leaves had been reported to contain bioactive compounds with gastroprotective potential. Objectives: This study investigated the protective effects of 70% ethanolic extract of C. barbata leaves on ethanol-induced gastric ulcers in rats. Methods: Thirty male rats were randomly allocated into six groups. The groups consisted of a normal control, a negative control (Na CMC 0.5%), a positive control (ranitidine 13.5 mg/kg BW), and three treatment groups that received C. barbata ethanolic extract at doses of 100, 200, and 400 mg/kg BW. Treatments were administered orally for 14 consecutive days, and the animals were sacrificed on day 15. Ulcer count, ulcer diameter, ulcer index, and gastric pH were assessed. Results: The negative control group exhibited an average of 6.4 ulcers. Administration of ranitidine and all tested concentrations of C. barbata extract significantly reduced the number of ulcers compared to the negative control. The most pronounced effect was observed at 400 mg/kg BW, yielding an average of 1 ulcer and a significantly lower ulcer index (p < 0.05). In contrast, gastric pH values showed no significant differences among the treatment and negative control groups (p > 0.05). Conclusions: The findings indicated that the ethanolic extract of C. barbata leaves exerted gastroprotective activity, with the 400 mg/kg BW dose demonstrating the strongest ulcer-preventive effect.